2020
DOI: 10.3390/ijerph17176029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Indoor Pollution from Glo, Iqos, and Juul, Using Traditional Combustion Cigarettes as Benchmark: Evidence from the Randomized SUR-VAPES AIR Trial

Abstract: Modified risk products (MRP) such as electronic vaping cigarettes (EVC) and heat-not-burn cigarettes (HNBC) are appealing alternatives to combustion cigarettes. Limited between- and within-device comparative data are available on MRP. We aimed at comparing indoor particulate matter (PM) emissions measured in a randomized trial enforcing standardized smoking sessions, testing different devices and flavors of MRP, using traditional combustion cigarettes (TCC) as benchmark. Overall, MRP yielded significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 51 publications
3
4
0
Order By: Relevance
“…Size-segregated mass size fraction concentration measurements confirmed, as presented in Figure 1 , that all the devices emit very fine particles, with a dynamic diameter <1μm, at a percentage higher than 99.7%. This is in accordance with previously published works 24 , 33 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Size-segregated mass size fraction concentration measurements confirmed, as presented in Figure 1 , that all the devices emit very fine particles, with a dynamic diameter <1μm, at a percentage higher than 99.7%. This is in accordance with previously published works 24 , 33 .…”
Section: Discussionsupporting
confidence: 93%
“…The results for different devices and use conditions present significant variations. Foster et al 22 found 6.5–10.3μg/m 3 PM 1 , 6.6–10.7 μg/m 3 PM 2.5 , 6.0–12.8 μg/m 3 PM 10 , during use of THP1.0 under three different ventilation conditions, Mitova et al 23 measured both PM 1 and PM 2.5 <11 μg/m 3 during use of THS 2.2 under natural ventilation, and TPM using two different brands, IQOS and GLO, under the same conditions, was 39 (24–127) μg/m 3 (GLO) and 31 (20–63) μg/m 3 (IQOS) 24 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, as discussed below, the use of a metal blade as a tobacco heating element in the case of HTPs normally releases significant amounts of debris, fluids, and fragments of cast left in the holder and, for this reason, it is necessary to clean the devices after 20 tobacco sticks. The most common devices use the blade to heat the tobacco sticks; however, new heating systems have been developed, such as an induction heating chamber (Glo TM ), where tobacco sticks are placed inside the device, and the use of an external resistive heater made of stainless-steel tracks is utilized [ 43 ].…”
Section: The Ends Devicesmentioning
confidence: 99%
“…The emissions of PM in confined spaces were assessed when smoking traditional cigarettes and using non-combustible tobacco products. Peruzzi et al showed in the randomised trial that using non-combustible tobacco products leads to significantly lower levels of indoor PM in comparison to classic cigarettes [ 62 ]. A similar study was performed by Protano et al where PM with an aerodynamic diameter smaller than 10, 4, 2.5 and 1 µm (PM10, PM4, PM2.5, PM1) were measured indoors after using alternatives to conventional cigarettes.…”
Section: Toxicant Emissionmentioning
confidence: 99%